Author Correction: A sulfotransferase dosage-dependently regulates mouthpart polyphenism in the nematode Pristionchus pacificus. Issue 1 (December 2018) - Bui, Linh; Ivers, Nicholas; Ragsdale, Erik
The original version of this Article contained errors in Figure 4. In panel a, thex axis labels of bars 6-11 were incorrect, as depicted in the associated Author Correction. These errors have been corrected in both the PDF and HTML versions of the Article.